Numerical and Experimental Analysis of Stacking Sequences Effects in Composite Mechanical Joints under Impact Loadings (Fracture and Structural Integrity, 2020)
Composite structures in the field of advanced and modern structures in engineering design and according to high specification of composite materials such as high strength to weight ratio use in various industries such as aerospace, marine. One of the most important fields that Researchers have paid less attention to that is to investigate the effect of stacking sequence on the strength of mechanical joints under impact loading. In view of changing the mechanical properties of composite materials by changing the arrangement of layers, in this study, the effect of different orientation of layers on the strength of pin joints in glass-epoxy composites under low-velocity tensile impact has been investigated. Using the Abaqus software and the finite element method, the impact simulation and the force applied to the mechanical joint were analyzed. To evaluate the simulations, the results of the finite element method have been compared with the experimental results. By observing the results, the introduced finite element model is well-considered and is well-matched with the result of the experimental dataset, which made it a valuable tool for predicting the strength of multi-layer composite materials under impact loadings. Using the results of the model, one can analyze the distribution and type of stress and strain in each layer of composite.
Keywords: Composites; Mechanical Joint; Joints Strength; Stacking Sequence; Tensile Impact